THE EFFECTIVENESS OF TRANSCRANIAL MAGNETIC STIMULATION IN PEDIATRIC NEUROLOGICAL DISORDERS (International journal of medical sciences, 2026)
Pediatric neurological disorders are frequently associated with motor, cognitive, and behavioral impairments that significantly affect quality of life and functional independence. In recent years, transcranial magnetic stimulation (TMS) has emerged as a non-invasive neuromodulation technique with potential therapeutic benefits in children with neurological conditions. This article analyzes the effectiveness of transcranial magnetic stimulation in the management of pediatric neurological disorders, including cerebral palsy, epilepsy, attention-deficit hyperactivity disorder, and post-stroke motor dysfunction. The review highlights the mechanisms of action, clinical outcomes, and safety considerations of TMS in pediatric populations. Available evidence suggests that TMS can improve motor function, cognitive performance, and neuroplasticity when applied in a controlled and individualized manner. Understanding the therapeutic potential of TMS is essential for integrating this technology into pediatric neurorehabilitation.